Predictors of Success and Status of College Students - Crookshanks, J. Doug (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to assess the ability of entrance tests as well as selected background variables to predict grade-point average among first-term full-time freshmen enrolled in an Alberta college. The entrance tests included a global measure of mental ability,a measure of reading comprehension, and two scales which purport to measure achievement motivation. Background variables included age, sex, and last completed grade of each student. None of the entrance tests were able to differentiate between dropouts and non-dropouts. The mental ability test was a significant predictor within certain academic programs.